Isolation and appraisal of a non-fermentative bacterium, Delftia tsuruhatensis, as denitrifying phosphate-accumulating organism and optimal growth conditions. (August 2020) - Li, Huankai; Liu, Hui; Zeng, Qingqing; Xu, Mingyu; Li, Yiyong; Wang, Wei; Zhong, Yuming
Abstract: Eutrophication caused by excessive nitrogen, phosphorous in water body has considerably serious impacts on the production and life of human being. Activated sludge, a biological removal process, is regarded as a promising and sustainable technology for wastewater treatment. In this study, a novel strain of denitrifying phosphate-accumulating organism (DPAO) was isolated from the activated sludge conducted the acclimation of anaerobic/anoxic (A/O) stage and anaerobic/aerobic (A/A) stage. The removal efficiencies of NO3 − -N and PO4 3- -P in bioreactor were 98.7 % and 90.7 % respectively. The metabolic activity of DPAOs was improved from 34.43%–98.28% after A/A stage. The genetic identiﬁcation and morphological and biochemical characteristics of isolated strain were analyzed and discussed to determine it as a non-fermentative Delftia tsuruhatensis . Sodium acetate and ammonium sulfate + peptone were testified to be optimal carbon source and nitrogen for the growth of this strain respectively. Furthermore, the orthogonal test was measured and calculated to find that the order of key factors affecting the growth of this strain was pH > nitrogen > carbon. According to computer response surface methodology, the most suitable medium group for this strain as 4450 mg/L of sodium acetate (carbon source), 1320 mg/L of ammonium sulfate + peptone (nitrogen source) and 7.85 of pH. The ﬁndings of this work broadened up our comprehension of the biological removal process for DPAOs during enhanced biological phosphorus removal.